2020
DOI: 10.15244/pjoes/111320
|View full text |Cite
|
Sign up to set email alerts
|

Invasion Impact Analysis of <i>Broussonetia papyrifera</i> in Pakistan

Abstract: Phytosociological studies help to understand extent of biological invasion. The current study assessed impact of Broussonetia papyrifera invasion on native vegetation in Pothwar region of Pakistan. The approach used for study was random samplings with two categorical factors; invaded and non-invaded (control) under same habitat conditions. Differences in number of species (S), abundance (N), species richness (R), evenness (Jꞌ), Shannon diversity index (Hꞌ) and Simpson index of dominance (λ) were compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Compound 91 showed inhibitory activity against tyrosinase, while compound 92 exhibited cytotoxic activity against three cancer cell lines (NCIH1975, HepG2, and MCF-7), and compound 89 inhibited the production of IL-2 in Jurkat cells [41]. In 2020, the structures of several compounds (43,(84)(85)(86)(87)(88) were elucidated, based on NMR and HRMS data, showing that compounds 43 and 86 could be used for inflammatory diseases [42]. Compounds 53, 54, 55, 57, 62, 64, 65, 66, 67, 68, 72, 77, 79, 80 and 81 were reported by Qureshi et al [43].…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 91 showed inhibitory activity against tyrosinase, while compound 92 exhibited cytotoxic activity against three cancer cell lines (NCIH1975, HepG2, and MCF-7), and compound 89 inhibited the production of IL-2 in Jurkat cells [41]. In 2020, the structures of several compounds (43,(84)(85)(86)(87)(88) were elucidated, based on NMR and HRMS data, showing that compounds 43 and 86 could be used for inflammatory diseases [42]. Compounds 53, 54, 55, 57, 62, 64, 65, 66, 67, 68, 72, 77, 79, 80 and 81 were reported by Qureshi et al [43].…”
Section: Flavonoidsmentioning
confidence: 99%
“…In 2020, the structures of several compounds (43,(84)(85)(86)(87)(88) were elucidated, based on NMR and HRMS data, showing that compounds 43 and 86 could be used for inflammatory diseases [42]. Compounds 53, 54, 55, 57, 62, 64, 65, 66, 67, 68, 72, 77, 79, 80 and 81 were reported by Qureshi et al [43]. In 2021, six previously undescribed prenylated flavonoids, compounds 32, 33, 34, 36, 39, and 42, and three known compounds, 35, 41, and 44, were isolated from the roots of BK; compounds 32, 33, and 36 showed strong dosedependent antiosteoclastogenic activities [44].…”
Section: Flavonoidsmentioning
confidence: 99%
“…heat tolerance and short rotation period (Adigbli et al 2019;Qureshi et al 2020). The leaves of BP contain 21.6% of crude protein, 4.3% of ether extract, and 1.9% of calcium (Wu et al 2019).…”
mentioning
confidence: 99%
“…The competitive advantage of invasive plants over native plants for resources seriously affects the growth of the local plants [34]. The results of our study demonstrated that the growth of G. uralensis under interplanted conditions was significantly inhibited by strong competition from X. italicum.…”
Section: Discussionmentioning
confidence: 64%